PENGARUH PRICE DISCOUNT, BONUS PACK, DAN VARIETY SEEKING TERHADAP BRAND SWITCHING SUSU ANLENE KE MEREK LAIN DI FOODMART BASKO GRAND MALL PADANG - Desi Wahyuni; Tri Kurniawati (Jurnal Ecogen, 2018)
The research aims to understand of the influence of price discount, bonus pack and variety seeking toward Brand Switching Anlene Milk to the other product in Foodmart Basko Grand Mall Padang. The purpose of this research are: 1) the effect of price discount toward brand switching milk anlene to the other product in Foodmart Basko Grand Mall Padang, 2) the effect of bonus pack toward brand switching milk anlene to the other product in Foodmart Basko Grand Mall Padang, 3) the effect of variety seeking toward brand switching milk anlene to the other product in Foodmart Basko Grand Mall Padang. The type of research used in this study is a causal quantitative research. The population in consumer of Basko Grand Mall Padang. The sampling technique is purposive sampling method with the total samples of 100 people. The type of data used is primary and secondary data. The data analysis technique used is multiple regression by using t test and F test. The result of the research show that there are a positive and insignificant influence between price discount (X1) variable on brand switching behavior of milk anlene to the other product in Foodmart Basko Grand Mall Padang, bonus pack (X2) significantly influence the brand switching behavior of milk anlene to the other product in Foodmart Basko Grand Mall Padang, and variety seeking (X3) significantly influence the brand switching behavior of milk anlene to the other product in Foodmart Basko Grand Mall Padang.Keywords: price discount, bonus pack, variety seeking, and brand switching